A Cultural History of Bilingual Charters from Catalonia: Language and Identity - Peri, Mikhah (The Jewish quarterly review, 2021)
This study concentrates on bilingual charters from tenth- and eleventh-century Catalonia. It shows that Jews participated in the Christian bureaucracy and that Hebrew was incorporated into Latin deeds. Furthermore, local Latin formulas and documents were internalized into the Hebrew formulas and subsequently into the Jewish legal system in this region and era. After offering a survey of this corpus, the article attempts to provide a cultural history of these documents, with particular attention to questions of language and identity, by understanding their place within a predominantly oral and visual culture. Through a comparison of Hebrew formulas in Catalonian bilingual deeds with Latin and Aramaic formulas, it argues that the use of Hebrew was a cultural choice that served as an identity marker. Furthermore, the use of the Hebrew alphabet became the Jewish signum, the graphic symbol representing the Jewish self, conveying a message of an acceptable, even equal, Jewish identity within a Christian culture. Thus, Jewish landowners selected Hebrew not as a rejection of Latin but within the context of increasing engagement with the Christian legal system. The choice of Hebrew by this economic circle predates, and may have ushered in, the intellectual turn toward Hebrew in the same region during the late eleventh and twelfth centuries, known as the "translation movement."